Improving Basketball Skills Through Coordination Exercises in Pair for Middle School Students - PAȘCAN, Adrian; MOCA, Cosmin (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2024)
This paper aims to present effective methods for teaching exercises during physical education and sports lessons by performing exercises in pairs. The presence of a partner and/or opponent not only adds a competitive element but also simulates adaptation to unpredictable changes, thus creating conditions similar to those encountered in a real basketball game and providing more realistic feedback on the applicability of technical procedures in basketball. Materials and Methods: The subjects included in the study were represented by two fifth-grade classes (one experimental class and one control class) from “Ion Agârbiceanu” Secondary School in Cluj-Napoca. Initial tests were applied to both groups involved in the research, then the experimental group was subjected to a variety of pair exercises, followed by the same tests being applied to both groups again at the end. Results: The results obtained from the two tests applied to both groups in the research show a more visible progress in the experimental group, especially in the second test, where a very large difference can be seen. In the experimental group, 18 out of 20 students improved their shooting percentage, while in the control group, only 5 achieved this. Conclusions: Based on the results obtained, we can confidently state that applying pair-specific basketball exercises improved the execution of procedures and technical elements.